1974
DOI: 10.1159/000193108
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Central Chemoreceptor Function and Chronic Hypoventilation Many Years Following Poliomyelitis

Abstract: A 41-year-old slender female who had led an active life presented with heart failure. Some months later she became comatose with severe hypercapnia and hypoxemia following a mild sedative and antihistaminic. Studies demonstrated normal respiratory and cardiac mechanics, a normal peripheral and an absent central chemoreceptor response. Ventilatory response to exercise was normal. Hypercapnia and hypoxemia were reversed by voluntary hyperventilation and became more severe during sleep. We suggest that central ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1974
1974
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…lt has been reported that some individuals with bulbar polio (P BM) have measurable dysfunction of respiratory control and irregular breathing during sleep [8,10). However, our group of bulbar polio survivors had nonnaJ respiratory mechanics with the exception of a slight reduction in expiratory muscle strength.…”
Section: Discussioncontrasting
confidence: 53%
“…lt has been reported that some individuals with bulbar polio (P BM) have measurable dysfunction of respiratory control and irregular breathing during sleep [8,10). However, our group of bulbar polio survivors had nonnaJ respiratory mechanics with the exception of a slight reduction in expiratory muscle strength.…”
Section: Discussioncontrasting
confidence: 53%
“…In some, but not all of the cases there is a history of a previous neurological disorder such as encephalitis, meningitis, Parkinsonism or poliomyelitis. Twenty-two separate case reports in which exercise was studied have been reviewed by Solliday, Gaensler, Schwaber & Parker (1974). All cases were hypercapnic and hypoxic when at rest; upon mild exercise, seven had no change in blood gases, five improved and ten had worsening blood gases.…”
Section: Previous Exercise Studies In Adults With Alveolar Hypoventilmentioning
confidence: 99%
“…The goal again was to prevent hypoxemia and hypercarbia during the hours of rest. [23][24][25] Two patients in Group V required total support of mechanical ventilation. However, the goal in two patients with diaphragmatic paralysis was providing rest for the accessory muscles of respiration at night and preventing severe hypoxemia, particularly during REM sleep.…”
Section: Discussionmentioning
confidence: 99%